The Effect of Environmental Performance and Corporate Social Responsibility Disclosure on Financial Performance (Study on Basic Industry and Chemical Companies listed on Indonesia Stock Exchange) - Natalia, Yessica; Subekti, Imam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The objective of this study is to examine the effect of environmental performance and Corporate Social Responsibility disclosure on financial performance. Environmental performance is measured by the companies’ performance in the PROPER rating program by Indonesian State Minister for the Environment, while the disclosure of corporate social responsibility is measured by the index of Global Reporting Initiatives. Corporate financial performance is measured by calculating the company's stocks expected return. This research was conducted by testing the hypothesis, aimed to explain the phenomena of the relationship among variables. The hypothesis one examines the effect of environmental performance on corporate financial performance. Then, the hypothesis two examines the effect of Corporate Social Responsibility disclosure on corporate financial performance. The samples of this study are 55 Basic Industry and Chemical Companies. The data was obtained from annual reports of the companies listed on Indonesia Stock Exchange and joined PROPER program from 2010 to 2012. Hypothesis analysis used in this study is multiple linear regressions. The findings of this study showed that environmental performance, Corporate Social Responsibility disclosure, and predetermined variable that is earnings per share are the significant variables to determine the dependent variable (corporate financial performance). Keywords: Environmental Performance, Corporate Social Responsibility Disclosure, predetermined variable, Corporate Financial Performance